Injury Detection in Traumatic Death: Postmortem Computed Tomography vs. Open Autopsy. (March 2020) - Wijetunga, Chatura; O'Donnell, Chris; So, Tiffany Y; Varma, Dinesh; Cameron, Peter; Burke, Michael; Bassed, Richard; Smith, Karen; Beck, Ben
Highlights: Post-mortem CT (PMCT) and autopsy both detected a considerable number of injuries that were missed by the other modality. For AIS-coded injuries, the kappa value for agreement between PMCT and autopsy for presence of injury was moderate for the majority of injury regions including head, thoracic organs, upper extremity, pelvis and skeletal chest injuries (κ = 0.45–0.58). The injury regions with highest agreement between PMCT and autopsy was in the lower extremity (κ = 0.69) and the lowest agreement was seen among abdominal and vascular injuries (κ = 0.07 and 0.10 respectively). PMCT was superior in detecting bony injuries and abnormal gas accumulations and autopsy was better able to detect soft tissue injuries and vascular injuries. When PMCT imaging of injuries detected by autopsy but missed by PMCT were reviewed again, subtle but inconclusive findings could be observed in many (but not all) injuries. A combination of PMCT and autopsy will identify more injuries than either modality alone. Abstract: Objective: To compare postmortem computed tomography (PMCT) vs. autopsy in detecting and analyzing injuries due to traumatic deaths. Materials and methods: In this retrospective study, a cohort of 52 subjects were purposively sampled to reflect a broad range of injuries. Injuries from autopsy and PMCT reports were coded using the Abbreviated Injury Scale (AIS) and the level of agreement of AIS 2+ and 3+ injuries were compared. Results: A combined total of 353 AIS-coded injuries were detected - PMCT detected 63% and autopsy detected 74% of injuries. PMCT identified 92 (26%) additional injuries missed by autopsy. PMCT missed 131 (37%) injuries. The kappa value for agreement between the two modalities for presence of injuries was moderate for the majority of anatomic regions [head (κ = 0.53), thoracic organs (κ = 0.58), upper extremity (κ = 0.53), pelvis (κ = 0.45), skeletal chest injuries (κ = 0.57)]. Kappa value was least among abdominal (κ = 0.07) and vascular injuries (κ = 0.10). Substantial agreement (κ = 0.69) was present in lower extremity injuries. PMCT outperformed autopsy for bony injuries, in particular, pelvic injuries, base of skull fractures and upper extremity injuries. PMCT better detected pneumothoraces. Soft tissue injuries, particularly abdominal organ injuries, lung contusions and vascular injuries were better detected by autopsy. When injuries missed by PMCT were re-assessed, subtle but inconclusive imaging findings were identified. Conclusion: A combination of PMCT and autopsy can detect more injuries than either modality in isolation. PMCT detected a considerable number of injuries missed by autopsy and vice versa.